APLIKASI BAND RATIO NDMI CITRA LANDSAT 8 DALAM PENENTUAN ZONA RAWAN LONGSOR DENGAN METODE OVERLAY ANALYSIS - Vinansius Jimmy Jati; Sari Bahagiarti Kusumayudha; Tedy Agung Cahyadi (KURVATEK, 2020)
Generally disaster research specifically identifies landslide-prone zones, over large areas with extreme terrain, usually secondary data on soil depth and texture are very rarely available, compared to topographic data, rock types, rock distribution and rainfall data. As an alternative the remote sensing method uses Landsat 8 imagery with the Normalized Difference Moisture Index (NDMI) band ratio method, the NDMI band ratio is able to identify the soil surface moisture index so that it can be interpreted with textures and soil depth related to the level of landslide vulnerability. With the method of overlay analysis using geographic information system (GIS) software, it is considered capable of analyzing the level of landslide vulnerability, especially in research on a regional scale, in remote areas that are difficult to access, based on secondary data availability. Keywords: Landsat, NDMI, Landslides, GIS